An Intact U5-Leader Stem Is Important for Efficient Replication of Simian Immunodeficiency Virus - Guan, Yongjun (American Society for Microbiology, 2001)
Previous work has shown that four deletions in simian immunodeficiency virus (SIV), termed SD1a, SD1b, SD1c, and SD6, which eliminated sequences at nucleotide positions 322 to 362, 322 to 370, 322 to 379, and 371 to 379, respectively, located downstream of the primer binding site, impaired viral replication capacity to different extents. Long-term culturing of viruses containing the SD1a, SD1b, and SD6 deletions led to revertants that possessed wild-type replication kinetics. We now show that these revertants retained the original deletions in each case but that novel additional mutations were also present. These included a large deletion termed D1 (nt +216 to +237) within the U5 region that was shown to be biologically relevant to reversion of both the SD1a and SD1b constructs. In the case of SD6, two compensatory point mutations, i.e., A+369G, termed M1, located immediately upstream of the SD6 deletion, and C+201T, termed M2, within U5, were identified and could act either singly or in combination to restore viral replication. Secondary structure suggests that an intact U5-leader stem is important in SIV for infectiousness and that the additional mutants described played important roles in restoration of this motif.